DEVELOPMENT OF KAMPUNG WISATA LAWAS MASPATI SURABAYA AS TOURISM HERITAGE IN GOOD TOURISM GOVERNANCE PERSPECTIVE - Reza Tri Wahyuni; Ertien Rining Nawangsari (DIA: Jurnal Administrasi Publik, 2021)
The Surabaya City Government is developing a tourism program, namely Kampung Wisata. Kampung Lawas Maspati is one of the tourism potentials to be used as leading heritage tourism in the city of Surabaya. However, the Covid-19 pandemic has had an impact on the decline in tourists. This study aims to describe and analyze the development carried out so that tourism can continue to run in the midst of a pandemic by using the concepts of good tourism governance principles, Bambang Sunaryo (2013). This type of research is qualitative research with data collection techniques in the form of observation, interviews, and documentation. The research location is in the Kampung Wisata Lawas Maspati Surabaya. The focus of the research is the application of the principles of good tourism governance in the development of Kampung Lawas Maspati. Research data sources, primary data and secondary data. The results of the study indicate that in the application of the ten principles of good tourism governance, there are two principles that have not been achieved and implemented properly, namely the principle of environmental carrying capacity and the principle of Program Monitoring and Evaluation.